Mongolia in Northeast Asia: Issues of Economic Development and Cooperation - Khaisandai, Luvsan (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i17.81 Mongolian Journal of International Affairs, No.17 2012: 59-63